MENINGKATKAN MINAT DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN KOOPRERATIF TIPE THINK – PAIR – SHARE - Arini Sofiana Fadhillah; Istiqomah Istiqomah (UNION: Jurnal Ilmiah Pendidikan Matematika, 2016)
The purpose of this research was to improve the learning interest and learning outcomes in mathematic of student of class VIII A SMP Al Ma’arif Bantul using cooperative learning type Think – Pair – Share (TPS). The subjects of this research was student of class VIII A SMP Al Ma’arif Bantul totaling 20 student. The object of this research was learning interest and mathematic learning outcomes. The result showed that after application of using cooperative learning type Think – Pair – Share in class VIII A SMP Al ‘ Ma’arif Bantul, learning interest and mathematic learning outcomes of student has increased. This was indicated by an increase in the result percentage average learning interest score of 73,8% in the pre-action, whereas at the first cycle improves with average percentage 81,00%. In the second cycle improve to 89,21%. Mathematic learning outcomes of student also increased. At the beginning of the test the ability is 35,65. In the first cycle, the average result improves to 57,33. In the second cycle the average result improves to 72,5.